Bekasam, an Indonesian unique traditional fermented fish as umami sources - Miftachurrochmah, Anis; Fibrianto, Kiki; Sunarharum, Wenny Bekti (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
Bekasam is a fish that is spontaneously fermented by adding salt and a source of carbohydrates (such as cooked white rice). This traditional food is often found in several regions of Indonesia, especially in South Sumatra, South Kalimantan, and North Sulawesi. Bekasam is traditionally produced to preserve fish during the harvest season. This review aims to present information on the historical background of bekasam, its manufacturing process, chemical characteristics, the types of microflora that exist within it, and the potential utilization of bekasam as a source of umami in dishes. The methodology for this study included a combination of literature review, observational interviews with traditional bekasam producers, experimental bekasam processing, and thorough documentation. A total of 60 articles were collected and chosen based on appropriate criteria. The results of the review article offer several explanations, based on historical aspects bekasam is an adaptation of Chinese cuisine introduced by traders who visited Sriwijaya. In the South Sumatra region, especially among the Ogan and Komering tribes, clay jars left by the Chinese are used to store bekasam in the kitchen. The Komering tribe refers to the fermentation of bekasam as sam-sam.  Various microbes are found in bekasam, with the main constituent being Lactobacillus spp., and a significant presence of Lactobacillus plantarum. During fermentation, the proteins in the raw materials of bekasam are degraded into simple compounds, mainly amino acids. Glutamate and aspartate had the highest values in the total composition of the other amino acids. These two amino acids contribute to the umami taste of food products. After exceeding the threshold for glutamate and aspartate, bekasam has the potential to contribute to the umami taste. Due to its umami potential, bekasam has been developed into various cuisines, including fried bekasam, sautéed bekasam, and chili sauce.